Studies On Surface Aeration In Circular Tanks - Patel, Ajey Kumar (2011)
Water is a fundamental need for existence of mankind. Only 0.01 % of total global water is readily available for human consumption as fresh water. The rapid increase in human population and consequent rise in urbanization and industrialization is producing a stress on this meager water resource. Water at the same time is a renewable resource, ie with suitable treatment it can be made re-useable. Aeration is one of the important processes employed in activated sludge process of the biological treatment units of wastewater. In this process the level of dissolved oxygen in the effluent is raised to the required amounts to decompose organic matters present in the effluent and thereby to reduce the BOD (biochemical oxygen demand) of the effluent by a physical means called “aeration process”. The aeration process consumes as much as 60-80% of total power requirements of wastewater treatment plants. Therefore, the efficiency in design of aeration process is required so that treatment and its power consumption can be economized. With the objective of optimizing the aeration process the present work in this thesis endeavors to develop an aeration which is efficient as well as economical. The various geometric parameters that affect the aeration process in mechanical surface aerators have been optimized. In the present work circular surface aeration tanks have been used. There are two types of circular tanks: Baffled and unbaffled. Separate optimal geometric parameters have been obtained for baffled and unbaffled circular tanks. With optimal geometric similitude scale up studies were done. Reynolds number and Froude number criteria has been found unsuitable for scaling oxygen transfer rates. Theoretical power per unit volume parameter is the most suitable scaling parameter for oxygen transfer rates in both baffled and unbaffled circular tanks. Baffled circular tanks are found to give better performance in terms of oxygen transfer rates as compared to unbaffled tanks. In contrast unbaffled tanks give better performance in terms of power consumption as compared to baffled circular tanks. General correlations have been developed for oxygen transfer rates for both baffled and unbaffled circular surface aerations tanks which incorporate all the geometric and dynamic parameters. These correlations help in the design of new treatment facilities as well as evaluating and up gradation of existing facilities. Power consumption studies have also been conducted on circular surface aeration tanks. Geometric parameters affect the power consumption significantly. Using the optimal geometric similarity conditions obtained for oxygen transfer rates the scale up studies for power consumption has also been done. Reynolds and Froude criteria are found to be giving scale effects for non dimensional power consumption parameter, power number. Theoretical power per unit volume parameter is found to be the scaling parameters for power number and a suitable correlation equation has been developed for baffled circular surface aeration tanks. General correlations have been developed for power number in baffled and unbaffled circular tanks. A novel type of self aspirating tube sparger system has been developed. It is like a bubble aerator with a rotor. The various geometric parameters that affect oxygen transfer rates have been optimized in baffled circular surface aeration tank. The optimal geometrically similar tanks have been used for scale up studies. Theoretical power per unit volume parameter is found to be the scaling parameter for oxygen transfer rates in circular surface aeration tanks with self aspirating sparger systems. Circular baffled tanks with a special sparger system gives very much higher oxygen transfer rates (as much as 5.7 times) as compared to circular tanks. The oxygen transfer rates data from literature also show lower values as compared to the system developed in this thesis. Geometrically similar unbaffled tanks have also been used with self aspirating sparger system. For same power consumption oxygen transfer rate in circular surface aeration tanks with self aspirating sparger system is higher as compared to circular tanks without self aspirating system. Mixing mechanisms in surface aeration tanks depend upon two different extreme length scales of time, namely macromixing and micromixing. Small scale mixing close to the molecular level is referred to as micromixing; whereas macromixing refers to the mixing on a large scale. The effect of geometrical parameters on macromixing time has been studied. The scaling parameters for macromixing and micromixing have been developed and simulation equations governing these time scales are also presented.